Buah Pisang barangan (Musa acuminata linn) Sebagai Media Alternatif Perkembangbiakan Bakteri - Lubis, Retnita Ernayani; Sapitri, Alfi; Arisetya, Dian; Marbun, Eva Diansari (Herbal Medicine Journal, 2025)
Barangan banana (Musa acuminata linn) has an energy content of 89 calories, 22.84 grams of carbohydrates, 1.09 grams of protein and 0.33 grams of fat. The nutritional content and bioactive substances of barangan bananas have phenolics, anthocyanins and phenols. The purpose of this study was to determine whether barangan bananas can potentially be an alternative medium for bacterial growth. The growth method used in this study was the scratch method, with the calculation of the number of colonies using the TPC (Total Plate Count) method. The results of the study on the scratch method at various concentrations were able to grow optimally on barangan banana-based media at a concentration of 36%. The shorter exponential phase (log) period in the 36% concentration media with a higher cell density than in the 12% concentration media. Conclusion: Barangan banana (Musa acuminata linn) can potentially be an alternative medium for bacterial growth.